Pengembangan Website Pelayanan Terpadu Satu Pintu (PTSP) BMKG Ngurah Rai - Celia Maureen Chandra; Luh Arida Ayu Rahning Putri; I Putu Satwika; Agus Muliantara (Jurnal Pengabdian Informatika, 2026)
The development of the One-Stop Service (PTSP) website at BMKG Ngurah Rai aims to enhance efficiency and quality of public services in managing data and educational requests. This program includes situational analysis, website design, socialization, and evaluation. The website allows services, previously managed conventionally via letters and telephone, to be accessed more conveniently by the public. The development results show improvements in website responsiveness and ease of use, enabling the public to request weather data, insurance claims, internship applications, and study visits. This website is expected to significantly improve service quality at BMKG Ngurah Rai.